Low-Reflectivity Drusen With Overlying RPE Damage Revealed by Spectral-Domain OCT: Hint for the Development of Age-Related Macular Degeneration - Yang, Shasha; Gao, Zongyin; Qiu, Haijiang; Zuo, Chengguo; Mi, Lan; Xiao, Hui; Liu, Xing (Frontiers in Medicine, 2021)
Purpose: To observe the relationship between the characteristic changes in the drusen morphology revealed by the spectral-domain optical coherence tomography (SD-OCT) and the progression of age-related macular degeneration (AMD). Methods: A total of 380 drusen in 45 eyes in 35 patients with the intermediate drusen were longitudinally followed up every 6 months by SD-OCT for a period of 24 months. The drusen were divided into the dynamic group and stable group according to the following parameters: number, volume, concurrent retinal pigment epithelium (RPE)/ellipsoid zone (EZ) damage, and the development of advanced AMD. The morphological characteristics of the progressive or stable drusen were further analyzed. Odds ratios (ORs) and the risk for the drusen progression were calculated. Results: The level of interobserver and intraobserver agreement for each drusen tomographic morphological parameters ranged from 82.7 to 90%. At the end of an average follow-up of 15.92 ± 6.99 months, six patients developed choroidal neovascularization and no patients developed geographic atrophy. Finally, 139 drusen changed and 241 drusen remained stable. The drusen with low reflectivity (p < 0.001; OR: 5.26; 95% CI: 2.24–12.36), non-homogeneity without a core (p < 0.001; OR: 4.31; 95% CI: 2.08–8.92), RPE damage (p < 0.001; OR: 28.12; 95% CI: 9.43–83.85), and the EZ damage (p < 0.001; OR: 14.01; 95% CI: 5.28–37.18) were significantly associated with active change; the drusen with low reflectivity (p = 0.01; OR: 2.95; 95% CI: 1.29–6.75) and decreased overlying RPE reflectivity (p < 0.001; OR: 21.67; 95% CI: 9.20–51.02) were the independent predictors for progression. The drusen with high reflectivity were significantly associated with stabilization (p = 0.03; OR: 0.17; 95% CI: 0.04–0.84). Conclusion: Spectral-domain optical coherence tomography is an optimized, accurate, and efficient method to follow-up the drusen. The intermediate non-exudative AMD prognosis of the patient was most strongly correlated with the drusen reflectivity and disruption of the overlying RPE layer. The drusen with low reflectivity and overlying RPE damage were more likely to progress and required frequent follow-up.